FABRICATION AND EVALUATION OF HERBAL OINTMENT FORMULATIONS OF MORINGA OLEIFERA FOR TOPICAL DELIVERY - C Shaikh, Saddam; Sanap, Dnyaneshwar; Bhusari, Dipak V; Jain, Shirish; Kochar, Pooja P; Memon, Fahim S (Universal Journal of Pharmaceutical Research, 2018)
Objective: Traditional medicine is an important source of potentially useful new compounds for the development of chemotherapeutic agents. Moringa oleifera Lam. is a multipurpose and exceptionally nutritious vegetable tree with a variety of potential uses. It is distributed in many countries of the tropics and subtropics. Ointments are semisolid systems which behave as viscoelastic materials when shear stress is applied. They contain medicaments and are intended to be applied externally to the body or to the mucous membrane. Methods: In present study the Morenga oleifera leaves extract was used to formulate four different ointment formulations with different bases like cetostearyl alcohol, hard paraffin, and liquid paraffin. Formulations were evaluated for different parameters such as general appearance, spreadability, pH, extrudability, centrifugation, irritancy, loss on drying, stability study etc. Results: All formulations were found to be free of grittiness, homogeneous, without phase separation with green colour with a smooth homogeneous texture and glossy appearance. Viscosity of the ointment formulations was in the range of 32.21±0.51 to 35.3±0.4. Formulations were found to be stable at different temperature. Conclusion: On the basis of results it can be concluded that ointment preparations with extract of Morenga oleifera leaves indicated the suitability of method for the production of ointments. Peer Review History: Received 22 May 2018; Revised 6 July; Accepted 27 September; Available online 15 September 2018 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com